The Relationship of Consumer Perception of Muslim Students on Label Food Products Packaging with Their Purchase Decision Making - Yulia Rahmawati; Muktiarni Muktiarni (Universitas Muhammadiyah Mataram, 2018)
This research is motivated by the problems of food technology that has been growing rapidly at today, including the use of ingredients, which is the vital thing to be considered in its preparation. For Muslim community, the problem that arises is the number of food ingredients, both the main raw material and the additive material, which are difficult to trace their origin, whether they are from halal sources or not. There is also a public perception concerning the clarity or label of halal food products purchased. It would impact the decision purchase of food product. This study used a case method using questionnaire for Moslem students in UPI Department of Culinary Study Program. Correlational analysis was done to find the correlation of conception on label food with purchase decision making. The result shows that there is a sifnificant correlation between both respondents or consumers’ conception on label information of food ingredients and their purchase decision making. This is evident in the correlation which indicates the presence of a significant relation (r=0,546). It could be recomended that in any attempt to produce food, especially in Indonesia, food ingredients in terms of being halal and hygienic should be highly considered; therefore the producers should have a halal certificate of the authorities, which in this case Board of Indonesian Muslim Scholars (MUI).